Pastoral Inspirations of Blessed Stefan Cardinal Wyszyński, Primate of Poland, Left to the Church in Warmia - Ropiak, Sławomir (Studia Warmińskie, 2024)
The purpose of this paper is to present the teaching of the new Blessed to the Church in Warmia. They can be characterized by a few core ideas, which include: spiritual and pastoral service of the Primate of Poland towards the Diocese of Warmia, priestly formation enlivened by the message from Stoczek Warmiński, Marian devotion deepened in the silence of the retreat, a great sign in [heaven] the sky in Gietrzwałd, honor to St. Wojciech Bishop Martyr, spiritual and pastoral heritage of the coronation of Marian images. The relics of the beatified Stefan Wyszyński were brought to Olsztyn and Stoczek Klasztorny.